Design and Implementation of an Automatic Sorting Machine - Abu Khalaf, Islam; Abu Arafeh, Murad (Palestine Polytechnic University (PPU) - mechatronics, 2018)
Abstract Design and Implementation of Automatic Sorting Machine Sorting and recycling require fast and accurate processing. Millions of tons of scrap are processed each year moreover sorting scrap adds value at all stages of the material recycling process and then achieve a maximum price of the scrap. The main idea of our project is to design and implement a machine that sorts, and classifies three different types of materials which are iron, aluminum, and plastic. Then guide materials to different carts to prepare for the material recycling process. Materials are gravity-fed from the hopper to the conveyor. Then the entered materials are scanned by sensors (inductive and magnetic) that are connected to a programmable logic controller (PLC) which gives the order to air pistons that are located at the edges of the conveyor to move each type of materials to specific cart. Keywords: Sorting, Piston, Sensor.
CD, no of pages 64, 8/2018ميكاترونيكس, in the store
Keywords: Design, and Implementation, of an Automatic ,Sorting Machine